2019
DOI: 10.5964/ejop.v15i3.1633
|View full text |Cite
|
Sign up to set email alerts
|

Predictive attentional bias modification induces stimulus-evoked attentional bias for threat

Abstract: Attentional Bias Modification (ABM) aims to modulate attentional biases, but questions remain about its efficacy and there may be new variants yet to explore. The current study tested effects of a novel version of ABM, predictive ABM (predABM), using visually neutral cues predicting the locations of future threatening and neutral stimuli that had a chance of appearing after a delay. Such effects could also help understand anticipatory attentional biases measured using cued Visual Probe Tasks. One hundred and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Thus, performance on probes is never influenced by the direct presentation of an emotional stimulus, only by the location of visually neutral cues predicting stimulus categories. Further, it has been found that performing a training version of the cVPT induces an attentional bias to stimuli belonging to the trained predicted categories [24]. This supports the interpretation of effects on the cVPT being due to anticipatory processes.…”
Section: ■ Introductionsupporting
confidence: 63%
“…Thus, performance on probes is never influenced by the direct presentation of an emotional stimulus, only by the location of visually neutral cues predicting stimulus categories. Further, it has been found that performing a training version of the cVPT induces an attentional bias to stimuli belonging to the trained predicted categories [24]. This supports the interpretation of effects on the cVPT being due to anticipatory processes.…”
Section: ■ Introductionsupporting
confidence: 63%
“…Accordingly, a few authors have suggested that sham training actively trains equal attention to substance-relevant and neutral stimuli and thereby may affect control over attention for substance-related stimuli (e.g., Schoenmakers et al, 2010 ; Badura-Brack et al, 2015 ; Khanna et al, 2016 ). Others have suggested that sham training serves to train participants to ignore emotional stimuli when confronted with them (Gladwin, 2017 ; Gladwin et al, 2019 ). In line with these ideas, the sham training protocol has sometimes been reconceptualized and renamed as “attentional control training,” and viewed as a more top-down goal-directed process (Gladwin, 2017 ).…”
mentioning
confidence: 99%
“…Predicted outcomes would be expected to bias the selection of responses towards those with better predicted outcomes, including covert cognitive responses such as attentional shifts. Evidence that this outcomefocused automatic process does indeed underlie the anticipatory bias was provided by a training study: training participants to direct attention towards versus away from a cued salient stimulus category, using a predictive form of Attentional Bias Modification, was found to result in a subsequent stimulus-evoked bias (Gladwin, Möbius, & Becker, 2019).…”
mentioning
confidence: 99%